MANAGEMENT OF INSOMNIA - Rosdiana Sholehah, Liya (E-Jurnal Medika Udayana; vol 2 no5(2013):e-jurnal medika udayana, 2013)
Sleep is an essential component of health and well-being. The effects of insomnia, Whether as a primary or secondary symptoms, is a major health concern and should be closely studied and Examined across all age groups. There is growing evidence that the effects of insomnia on Adolescent's functioning is comparable to that of other major psychiatric disorders (eg, mood disorders, anxiety disorders, etc..). Insomnia is associated with significant negative Consequences, impairing functioning across a number of emotional, social, cognitive, and physical domains (Carskadon, 1999; Johnson, Roth, Schultz, & Breslau, 2006; Roberts, Roberts, & Duong, 2008b; Wolfson & Carskadon, 1998). Based on the academic literature to date, it is hypothesized that insomnia will be Significantly more prevalent   among   Adolescents   of   the   female   sex   and   among   those   reporting psychological and / or physical health concerns. The analyzes conducted included basic descriptive statistics (frequencies / percentages), bivariate analyzes (Chi-square tests), and a multiple logistic regression. The prevalence rate of insomnia in adolescents was 9.5%, with no significant association found between sex and insomnia. The multivariate analysis Showed Significantly insomnia to be associated with the presence of a chronic condition, selected mood disorders (12 months), in adolescents  who  are  experiencing  "quite  a  bit"  to  "extreme"  life  stress,  and  in adolescents who were living in than other households with both parents. Insomnia was not found to be associated Significantly with sex, selected anxiety disorder (12 months), heavy drinking, heavy cannabis use, and in Adolescents who were only experiencing "some life stress".  heavy cannabis  use  and  having  a selected  anxiety Significantly disorder was associated with insomnia. More informed knowledge can be used to create prevention and treatment strategies to address  Adolescent  sleep  problems.  By doing  this,  we  can  hopefully  mitigate  any negative impact of insomnia may have on the Adolescent's ability to  function and address the concerns before they Become chronic.
Keywords: insomnia, mental health, life stress, medication use